Developing a Phonotaxis Performance Index to Uncover Signal Selectivity in Walking Phonotaxis - Lee, Norman; Kirtley, Alexander T.; Pressman, Isaiah S.; Jirik, Karina J.; Koucoulas, Dean; Mason, Andrew C. (Frontiers in Ecology and Evolution, 2019)
Any sensory strategies that prey take to avoid eavesdropping predators will depend on the behavioural decisions of eavesdroppers. As these decisions are guided by the sensory processing of communication signals, accurate measurements of sensorimotor output will provide insights into signal preferences, parameters evaluated for signal recognition, and the perceptual and cognitive capacity of receivers. A number of techniques have been proposed for measuring walking phonotaxis (and taxis behaviour more generally). Consistent limitations of such measures are (1) that some animals cannot discriminate alternative signals when they occur simultaneously (i.e. overlapping in the spectral and temporal domain), or (2) some animals respond with low selectivity to stimuli presented in isolation, and (3) identifying appropriate dimensions of response variability is not straightforward. Here we document an approach to develop a sensitive phonotaxis performance index to quantify pulse rate selectivity in two distinct populations of the acoustic parasitoid fly Ormia ochracea. Using a spherical treadmill to measure tethered walking phonotaxis, we examined the ability of flies to track a switch in the broadcast location of test songs with varying pulse-rates. By applying an information-theoretic approach, we identified a set of response parameters that best predict a previously described pulse-rate preference. These parameters were incorporated into an index to describe temporal pattern selectivity during walking phonotaxis. Our study also revealed that in Floridian Ormia ochracea, the pulse rate preference function is not affected by the locomotor mode (walking vs flying) used in phonotaxis. Furthermore, we describe for the first time, pulse rate selectivity in Californian Ormia ochracea. Both populations have pulse rate preference functions with peak selectivity between 50 to 60 pps. Previous studies demonstrating natural differences in host song preferences (Floridian O. ochracea preferring Gryllus rubens and Californian O. ochracea preferring Gryllus lineaticeps calling songs) may be based on other temporal parameters aside from pulse rate. Finally, we discuss the advantages and limitations of our approach in quantifying signal selectivity. This approach can be applied broadly to study signal preferences in other acoustic parasitoid flies and potentially other eavesdroppers that exhibit taxis behaviours in response to the communication signals of prey.